INTEGRAÇÃO SUL-AMERICANA SOB A PERSPECTIVA DA CONVERGÊNCIA E HARMONIZAÇÃO DAS NORMAS INTERNACIONAIS DE CONTABILIDADE: REFLEXOS NA REGIÃO DE FRONTEIRA BRASIL-BOLÍVIA - Fabio Araujo Delgado (2023)
ABSTRACT: The International Accounting Standards were created with the objective of harmonizing accounting between countries, given the process of globalization and the technological advancement recognized worldwide, the need of users of accounting information, to have the same standard of financial statements, regardless of the particularities of each country, but at the same time, respecting their sovereignty. This work aims to evaluate the effects of international accounting harmonization between the border countries Brazil and Bolivia, seeking to know the treatment given by countries to the International Accounting Standards, in the light of the changes in Brazilian legislation, with the validity of Law 11,638/07 and 11,941/09, and also if there was a change in the Bolivian Legislation. Therefore, it was necessary to search the international literature for the origin and the main reasons for the emergence of the responsible body, the IASB, its real difficulties in the convergence towards a consensus on the use of International Accounting Standards, IFRS, the relevant changes in its formation, so that "today" it could become feasible and a reality in the face of the world scenario. We seek to present the main factors of influence, as to the differences between countries, the different schools, international accounting models and the characteristics of accounting in some countries, also highlighting the basic accounting curriculum presented by the UN, the main treatments given by MERCOSUR member countries, whether in the educational, professional aspect and regarding the harmonization and convergence to International Accounting Standards. In the result, we applied the same analyses of influence in the countries Brazil – Bolivia, object of this study, and how the educational and professional training reflect on the knowledge and use of International Accounting Standards. Based on the literature of each country, and through the application of a questionnaire, whose result is presented, shows that the countries studied already adopt the International Standards. Brazil, harmonizing, through a standardizing body (CPC) and Bolivia in an integral way, without there being a harmonization process. We consider in the end, that the objectives were achieved, without naturally having the intention of exhausting the theme, but aware that the process of adopting the International Accounting Standards is already a reality, as well as its importance in a universal Accounting. Keywords: IASB. IFRS. Accounting harmonization. MERCOSUL. CPC.